Long-Term Health-Related Quality of Life in Kawasaki Disease-Related Coronary Artery Aneurysm: A Large Single-Center Assessment in Nanjing, China - Yun Zhou, MD; Mei Chen, MD; Wenting Gao, MD; Yu Chen, MD; Ying Meng, MD (Texas Heart Institute Journal)
Background: The impact of coronary artery aneurysms (CAAs) caused by Kawasaki disease (KD) on long-term health-related quality of life (HRQOL) in children has not been well documented. Methods: This study investigated long-term HRQOL in a large sample of children diagnosed with KD-related CAAs. A case-control, retrospective study included 66 patients with KD-related CAAs. A total of 98 hospitalized patients were matched as controls based on age and sex: 49 patients were allocated to a group with pneumonia and 49 patients were allocated to a group with arterio-arterial fistula. Both child-reported and parent-proxy–reported Pediatric Quality of Life Inventory surveys were collected. Results: The median (IQR) follow-up period was 5.64 (3.81-7.47) years (range, 1.03-10.67 years). The mean (SD) age at diagnosis was 3.73 (1.93) years. At baseline, children and parents as their proxies reported similar HRQOL scores for KD-related CAAs and arterio-arterial fistula that were considerably lower than for pneumonia, respectively. At long-term follow-up, children in the small and medium-sized aneurysms group reported a mean (SD) score of 81.61 (19.50), which was comparable to the arterio-arterial fistula group (83.32 [18.24]), 9.51 points lower than that of the pneumonia group (P = .014), and 9.70 points higher than that of the giant aneurysms group (P = .012). Parents also reported a comparable mean (SD) score of 81.03 (12.57) vs 83.30 (15.17) in the small and medium-sized aneurysms group and arterio-arterial fistula group, both of which had statistically significantly lower scores than the pneumonia group (P = .010) and higher scores than the giant aneurysms group (P = .009). Conclusion: Despite improvement in HRQOL scores, children with documented KD-related CAAs without complete recovery often encountered issues that disrupted their well-being during long-term follow-up. Routine outpatient HRQOL screening could be instituted to help eliminate the risk of long-term disability following initial clinical improvement.